2019
DOI: 10.1021/acsmedchemlett.9b00091
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines as Inhibitors of Pre-microRNA Maturation: A Disconnection between RNA Binding and Inhibition

Abstract: In a high-throughput screening campaign, we recently discovered the rRNA-binding tetracyclines, methacycline and meclocycline, as inhibitors of Dicer-mediated processing of microRNAs. Herein, we describe our biophysical and biochemical characterization of these compounds. Interestingly, although direct, albeit weak, binding to the pre-microRNA hairpins was observed, the inhibitory activity of these compounds was not due to RNA binding. Through additional biochemical and chemical studies, we revealed that metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
(91 reference statements)
1
17
0
Order By: Relevance
“…The EDTA addition serves two purposes: (1) a reaction stop and (2) a methacycline decomplexation solution. With this amended protocol, we were then able to clearly detect methacycline inhibition of Dicer processing of f-pre-miR-21 at levels in general agreement with those reported by Garner et al 47 (Suppl. Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The EDTA addition serves two purposes: (1) a reaction stop and (2) a methacycline decomplexation solution. With this amended protocol, we were then able to clearly detect methacycline inhibition of Dicer processing of f-pre-miR-21 at levels in general agreement with those reported by Garner et al 47 (Suppl. Fig.…”
Section: Resultssupporting
confidence: 90%
“…The ability to detect Dicer inhibition by F-HT-MS assay using protocol B was demonstrated with two compounds: (1) EDTA, which sequesters the Mg 2+ required for Dicer activity, and (2) methacycline, which has been reported by Garner et al as an inhibitor of pre-miRNA cleavage by Dicer, although the exact mechanism is not clear. 47 The inhibition of Dicer activity as a function of EDTA concentration was readily observed as the EDTA concentration approached the MgCl 2 concentration of the assay buffer, but the effect of methacycline on miRNA maturation using the F-HT-MS assay required some modification as the signal intensity for both the internal standard 5 and f-RNA 4 cleaved loop decreased markedly as the methacycline concentration increased to the point where no signal was observed at 1000 µM methacycline. This was interpreted as oligonucleotide ion suppression by methacycline binding to both the f-DNA and the f-RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Once combined with Ago protein, the double strands are quickly unraveled, a chain is stabilized and the other is lost. The retention or degradation of the chain depends on its thermodynamic stability [ 24 , 25 , 26 ]. The mammalian Dicer/Ago/miRNA complex also interacts with a number of other proteins, such as Gemin3, Gemin4, Mov10, and GW182 [ 27 , 28 , 29 , 30 ].…”
Section: Micrornasmentioning
confidence: 99%
“…Small-molecule binding assays, such as fluorescence indicator displacement 21 require either selectively binding fluorophores or the displacement of more promiscuous probes, such as ethidium bromide, which can cause false negatives if the mode of binding differs. The hits from such assays have typically been verified by examining the maturation level of the pre-miR after adding the Dicer enzyme 16 and in several cases they have been furthered characterized using additional biophysical techniques such as isothermal titration calorimetry (ITC) 13 , differential scanning calorimetry (DSC) 14 or surface plasmon resonance (SPR) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that aminoglycosides 29 have a general affinity towards RNA 30 33 , including pre-miR-21 13 , 22 , 34 38 . However, the specificity of these binding events has yet to be fully elucidated 38 .…”
Section: Introductionmentioning
confidence: 99%